Aplikacja mobilna oparta na grywalizacji jako narzędzie zarządzania procesem kształcenia na poziomie studiów wyższych - Krysiński, Przemysław; Kowalska-Chrzanowska, Małgorzata; Królicka, Beata; Mielczarek-Taica, Anna; Pietrzak, Anna (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
The aim of this article is to present the stages of development of the gamified mobile application “Gra o dyplom” (Play for your diploma), created at Nicolaus Copernicus University in Toruń. It presents its functionalities (especially game-like elements, such as points, badges, feedback, levels, and rankings) and the potential for managing the students’ educational path. The application described in this article is a sensation on the Polish application market. Its uniqueness lies in the fact that it is not designed to gamify a specific subject or group of subjects, but the entire educational path.